Harnessing dividends from drylands innovative scaling up with soil nutrients - Raju, K. V.; Wani, S. P. (Suhas Pralhad), 1952- (CAB International, 2016)
This book brings together the results of a novel scaling-up initiative of the Bhoochetana Mission Program implemented during 2009-2012 in Karnataka. The second phase of Bhoochetana covers all 30 districts for both irrigated and dryland crops with strong leadership by the Government of Karnataka with technical support from ICRISAT. The book, consisting of 12 chapters, covers the micro to macro perspective, and describes in detail how the Bhoochetana Mission Program was conceived and has evolved to reach more than 5 million farmers in 4 years. The chapters describe soil nutrient mapping as a knowledge-based entry point for building rapport with the community and ensuring good community participation. New technologies such as geographical information system (GIS), information and communications technology (ICT), knowledge dissemination, monitoring and evaluation as well as analytical tools in addition to innovations in the areas of institutions, policies and delivery mechanisms have also contributed immensely to achieving the desired impact, and all these aspects have been covered in a number of chapters.